(untitled) (Physical Education, Health and Social Sciences, 2025)
Postharvest losses in horticultural commodities remain a major bottleneck in ensuring food and nutritional security worldwide. Fruits and vegetables, being highly perishable, suffer considerable quantitative and qualitative degradation due to physiological disorders, microbial decay, and inefficient postharvest handling. This review synthesizes current advancements in technological and biological interventions aimed at minimizing such losses and extending shelf life. Key strategies include pre-cooling, cold storage, and refrigerated transport as integral components of an optimized cold chain system, alongside controlled and modified atmosphere storage for maintaining product freshness. Edible coatings and biodegradable packaging materials have emerged as sustainable alternatives to synthetic plastics, offering improved moisture regulation and pathogen suppression. Non-thermal processing techniques such as UV-C irradiation and high-pressure treatments help retain nutritional and sensory quality, while smart sensors, machine learning, and IoT-enabled systems are revolutionizing cold-chain monitoring and decision-making. Integrated disease management approaches combining biological control agents, GRAS compounds, essential oils, and cultural practices present eco-friendly substitutes for synthetic fungicides. Collectively, these innovations contribute to improving product quality, marketability, and consumer safety while promoting environmental sustainability. The review highlights the need for scalable, cost-effective, and farmer-accessible technologies to ensure the broad adoption of sustainable postharvest solutions in both developed and developing economies.